Analysis of The Level of Patient Satisfaction with Pharmaceutical Services In Xyz Regional Hospital Bandung Indonesia - Devy Ike Mustika Sari; Muhammad Irfan Rizki; Dede Hertina (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Abstract Hospitals are health facilities that provide various services, one of which is pharmaceutical services. Pharmaceutical services are an activity organized to maintain and improve the health of patients. Patient satisfaction is an important indicator in achieving conformity with expectations in health services in hospitals. The level of patient satisfaction can be seen from good service. The purpose of this study is to determine and evaluate the level of patient satisfaction with pharmaceutical services at the XYZ regional hospital in Bandung, West Java. In this study, the application used in SPSS to process data with the methods used, namely the Importance Performance Analysis (IPA) method and the Customer Satisfaction Index (CSI). This method is used to identify the level of importance of each service attribute and the priority of improvements that must be made by a hospital to determine the level of patient satisfaction. IPA analysis shows that the point included in quadrant I (high importance and low satisfaction) is R6, namely complete available drugs but in reality, the drugs are not available so this statement is considered important by patients because it has facts that are not yet appropriate and need to further improve their performance so that the service is more satisfying. Meanwhile, based on the results of the CSI analysis, it is known that the overall value of the respondent's satisfaction level for all attributes is 83.9%. So based on the satisfaction index patients are satisfied with pharmaceutical services at the XYZ Bandung Regional Hospital.Keyword: Patient Satisfaction, IPA, CSI, Hospital